THE RELATION BETWEEN NURSES AGE AND COMPLIANCE IN THE IMPLEMENTATION OF PREVENTION OF FALLING PATIENTS IN THE GENERAL HOSPITAL OF THE SAMARINDA GOVERNMENT - M.Bachtiar Safrudin; milkhatun milkhatun (Jurnal Ilmu Kesehatan, 2019)
In the patient safety standards / International Patient Safety Goal (IPSG), especially the prevention of the risk of falling must be applied by nurses, age is one of the internal factors that affect compliance. This study aims to determine the correlation between age of nurses with adherence in the implementation of prevention of falling patients in Samarinda Government Hospital using a descriptive correlation design and cross sectional approach. The instrument used in this study was a questionnaire and observation sheet with a sample of 51 nurses in the non-intensive inpatient room with a purposive sampling technique. The analysis test in this study uses the Spearman rank test with the results of p value 0.026 (rho = 0.312), so it can be concluded that there is a significant influence between the age of nurses with adherence in the implementation of prevention of falling patients.